Superluminous supernovae: an explosive decade. Issue 5 (1st October 2021) - Nicholl, Matt
Abstract : Ten years on from the discovery of mysterious events 100 times brighter than conventional stellar explosions, Matt Nicholl charts our understanding of superluminous supernovae Abstract: Ten years on from the discovery of mysterious events 100 times brighter than conventional stellar explosions, Matt Nicholl charts our understanding of superluminous supernovae